Unraveling the evolutionary dynamics of the TPS gene family in land plants - Yan, Xue-Mei; Zhou, Shan-Shan; Liu, Hui; Zhao, Shi-Wei; Tian, Xue-Chan; Shi, Tian-Le; Bao, Yu-Tao; Li, Zhi-Chao; Jia, Kai-Hua; Nie, Shuai; Guo, Jing-Fang; Kong, Lei; et al. (Frontiers in Plant Science, 2023)
Terpenes and terpenoids are key natural compounds for plant defense, development, and composition of plant oil. The synthesis and accumulation of a myriad of volatile terpenoid compounds in these plants may dramatically alter the quality and flavor of the oils, which provide great commercial utilization value for oil-producing plants.Terpene synthases (TPSs) are important enzymes responsible for terpenic diversity.Investigating the differentiation of the TPS gene family could provide valuable theoretical support for the genetic improvement of oil-producing plants. While the origin and function of TPS genes have been extensively studied, the exact origin of the initial gene fusion event -it occurred in plants or microbes -remains uncertain.Furthermore, a comprehensive exploration of the TPS gene differentiation is still pending. Here, phylogenetic analysis revealed that the fusion of the TPS gene likely occurred in the ancestor of land plants, following the acquisition of individual C-and N-terminal domains. Potential mutual transfer of TPS genes was observed among microbes and plants. Gene synteny analysis disclosed a differential divergence pattern between TPS-c and TPS-e/f subfamilies involved in primary metabolism and those (TPS-a/b/d/g/h subfamilies) crucial for secondary metabolites. Biosynthetic gene clusters (BGCs) analysis suggested a correlation between lineage divergence and potential natural selection in structuring terpene diversities. This study provides fresh perspectives on the origin and evolution of the TPS gene family.